Developing organizational resilience from business process management maturity (INMR - Innovation & Management Review, 2023)
Objective: In the current business context, there is a current need to adopt contemporary practices of process management as a competitive advantage to leverage organizational results. This study aims to explore such relationships, considering the performance results in the organizational resilience dimension.Method: We collected 82 valid responses from a survey targeted at professionals occupying positions or functions in the operations area. For data analysis, we used the technique of structural equation modeling (SEM) using the PLS algorithm.Results: The results show that maturity in the management of business processes positively influences the behavior of organizational resilience, with the highest level of maturity primarily being responsible for this impact. This result reveals that resilience naturally depends on mature and well-established processes in the organizational structure. The proposed model explained 78.5% of organizational resilience.Practical/Theoretical Implications: Companies that maintain mature management of their business processes will be better able to positively influence organizational resilience since process management can make organizations less fragile supply chains and more adaptable to changes.Originality/Value: The findings helped clarify the extent to which process management influences the results of organizational resilience. Although the literature indicates that maturity in business processes is formed by five first-order constructs, only the “innovated” dimension proved to be significant in the present study.